OPTIMAL MEASURES FOR MINIMIZING THE TAX AUDIT EXPECTATION GAP IN KENYA - Limisi, Ebby Mutaka; McFie, Dr. James Boyd; Wang'ombe, Dr. David (European Journal of Business and Strategic Management, 2017)
Purpose: The purpose of this study was to find out whether a tax audit expectation gap exists between the tax authority and corporate tax payers. Methodology: The study adopted a descriptive research design. Findings: The study findings confirmed that, indeed, a tax audit expectation gap existed between corporate tax payers and the tax authority. In addition, better tax compliance standards, forensic accounting, I-tax implementation and user education were found to be important measures in narrowing this tax audit expectation gap. Unique contribution to theory, practice and policy: The study will be of significance to the following stakeholders: users of financial information including the corporate tax payers, the creditors, customers and suppliers. The study will provide information as to what is termed reasonable and unreasonable expectations. The tax authority in Kenya and those in other countries will find this study useful as it will highlight the tax audit expectation gap and how it can be reduced by several measures notably better tax compliance standards, forensic accounting, I-tax implementation, educating members and enhanced compliance with International Accounting Standards (IAS) and International Standards of Auditing (ISA). The findings of this study will also inform policy making with regard to corporate tax payers as pertains to duties and roles of auditors, the educative role of management, the introduction of stringent reporting and the government's role in supervising the affairs of corporate tax payers. This study will be an invaluable addition to literature pertaining to corporate tax payers, and measures for reducing the tax audit expectation gap. Scholars who wish to further their education on the area of the expectation gap may use the findings of this study to do so.